Winning at mergers and acquisitions : the guide to market-focused planning and integration - Clemente, Mark N.; Greenspan, David S. (New York : John Wiley, 1998)
This book presents the authors' ground-breaking blueprint for mergers that yield strategic synergies and high returns in meeting long-term growth, increased market share, and revenue generation objectives.
Includes index.
rua 23/02/15
Loans
Keywords: Consolidation and merger of corporations -- Planning